EphrinB2 activation enhances angiogenesis, reduces amyloid-β deposits and secondary damage in thalamus at the early stage after cortical infarction in hypertensive rats. Issue 9 (September 2019) - Xing, Shihui; Pan, Nannan; Xu, Wei; Zhang, Jian; Li, Jingjing; Dang, Chao; Liu, Gang; Pei, Zhong; Zeng, Jinsheng
Cerebral infarction causes secondary neurodegeneration and angiogenesis in thalamus, which impacts functional recovery after stroke. Here, we hypothesize that activation of ephrinB2 could stimulate angiogenesis and restore the secondary neurodegeneration in thalamus after cerebral infarction. Focal cerebral infarction was induced by middle cerebral artery occlusion (MCAO). Secondary damage, angiogenesis, amyloid-β (Aβ) deposits, levels of ephrinB2 and receptor for advanced glycation end product (RAGE) in the ipsilateral thalamus were determined by immunofluorescence and immunoblot. The contribution of ephrinB2 to angiogenesis was determined by siRNA-mediated knockdown of ephrinB2 and pharmacological activation of ephrinB2. The results showed that formation of new vessels and ephrinB2 expression was markedly increased in the ipsilateral thalamus at seven days after MCAO. EphrinB2 knockdown markedly suppressed angiogenesis coinciding with increased Aβ accumulation, neuronal loss and gliosis in the ipsilateral thalamus. In contrast, clustered EphB2-Fc significantly enhanced angiogenesis, alleviated Aβ accumulation and the secondary thalamic damage, which was accompanied by accelerated function recovery. Additionally, activation of ephrinB2 significantly reduced RAGE levels in the ipsilateral thalamus. Our findings suggest that activation of ephrinB2 promotes angiogenesis, ameliorates Aβ accumulation and the secondary thalamic damage after cerebral infarction. Additionally, RAGE might be involved in Aβ clearance by activating ephrinB2 in the thalamus.